Legal Transitions and the Problem of Reliance - Hasen, David M. (Columbia Journal of Tax Law, 2010)
This Article analyzes the literature on legal transitions. The principal focus is taxation, but the analysis generalizes to other areas. I argue that the theoretical apparatus developed by scholars active in the legal transitions area suffers from significant conceptual shortcomings. These shortcomings include the unwarranted assimilation of legal to factual change, the naturalization of conventional arrangements, and the disregard of the distinction between making law and finding it. As a consequence, the recent literature offers an analysis that is unable either to explain actual transitions or to provide an adequate theory of how legal change should take place. In the end, the older view of legal transitions is more capable than the newer one of providing an adequate normative and positive framework for understanding legal transitions.